1986
DOI: 10.1200/jco.1986.4.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced colorectal and gastric adenocarcinomas with 5-fluorouracil and high-dose folinic acid.

Abstract: We report the results of an expanded trial of 5-fluorouracil (5-FU) combined with high-dose folinic acid for treatment of patients with advanced colorectal or advanced gastric adenocarcinoma. In each treatment course, the patients received both 5-FU (340 to 400 mg/m2/d by intravenous (IV) infusion for a period of 15 minutes) and folinic acid (200 mg/m2/d by IV bolus) for 5 consecutive days, with a 21-day interval between courses. Eighty-six patients with colorectal carcinoma were evaluated. The combined comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
130
1
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(141 citation statements)
references
References 0 publications
6
130
1
4
Order By: Relevance
“…No clear trends were apparent in patients with Dukes' B2 disease. These results were confirmed in a later report after a median follow-up period of 6.5 years (Moertel et al, 1995 (Machover et al, 1986)] for 5 days every 28 days for six cycles. Of the 1493 evaluable patients, 736 were in the adjuvant treatment group and 757 were in the control (surgery only) group.…”
supporting
confidence: 68%
“…No clear trends were apparent in patients with Dukes' B2 disease. These results were confirmed in a later report after a median follow-up period of 6.5 years (Moertel et al, 1995 (Machover et al, 1986)] for 5 days every 28 days for six cycles. Of the 1493 evaluable patients, 736 were in the adjuvant treatment group and 757 were in the control (surgery only) group.…”
supporting
confidence: 68%
“…This regimen was first reported in 1991, with the three drugs being selected on the basis of their single agent activity in upper GIT tumours (Beer et al, 1983;Cersosimo and Hong, 1986;Machover et al, 1986), and on the synergy demonstrated between 5-FU and cisplatin in preclinical models (Etienne et al, 1991). ECF is associated with response rates of approximately 45% in patients with metastatic gastric cancer, although higher response rates are seen when used for locally advanced disease (Findlay et al, 1994;Waters et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal treatment regimen for these two drugs has not been unequivocally defined, the Mayo regimen of 5-FU and low-dose LV is widely regarded as an acceptable treatment and is the only regimen to have demonstrated a significant survival advantage over unmodulated 5-FU (Poon et al, 1989). However, other combination regimens, such as the Machover (5-FU with high-dose LV) regimen (Machover et al, 1986), or continuously infused 5-FU (Seifert et al, 1975;Lokich et al, 1989;de Gramont et al, 1995) are also used.…”
mentioning
confidence: 99%